2010
DOI: 10.1111/j.1365-2567.2009.03198.x
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic dietary protein guides maturation of the host immune system promoting resistance to Leishmania major infection in C57BL/6 mice

Abstract: Summary The immature immune system requires constant stimulation by foreign antigens during the early stages of life to develop properly and to create efficient immune responses against later infections. We have previously shown that intake of antigenic dietary protein is critical for inducing maturation of the immune system as well as for the development of T helper type 1 (Th1) immunity. In this study, we show that administration of an amino acid (aa)‐based diet during the development of the immune system su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
0
10
0
2
Order By: Relevance
“…Menezes et al ( 7 ) showed that exposure to food proteins after weaning plays a physiological role in inducing the maturation of the immune system both locally and systemically ( 7 ). Furthermore, it was demonstrated that mice fed a diet containing free amino acids from weaning to adulthood are more susceptible to Leishmania infection ( 9 ) and more resistant to induction of nasal and oral tolerance ( 10 , 11 ) as well as food allergy ( 11 ). In concert with these results, it has been shown recently that dietary proteins from solid food are responsible for the generation of the great majority of the small intestinal CD4+ Foxp3+ regulatory T cells involved in the induction of oral tolerance to food antigens ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Menezes et al ( 7 ) showed that exposure to food proteins after weaning plays a physiological role in inducing the maturation of the immune system both locally and systemically ( 7 ). Furthermore, it was demonstrated that mice fed a diet containing free amino acids from weaning to adulthood are more susceptible to Leishmania infection ( 9 ) and more resistant to induction of nasal and oral tolerance ( 10 , 11 ) as well as food allergy ( 11 ). In concert with these results, it has been shown recently that dietary proteins from solid food are responsible for the generation of the great majority of the small intestinal CD4+ Foxp3+ regulatory T cells involved in the induction of oral tolerance to food antigens ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…In both cases, intact dietary proteins were replaced by equivalent amounts of free amino acids as nitrogen source and they were shown to influence the maturation of the immune system, particularly the gut-associated lymphoid tissue when consumed from weaning to adulthood ( 7 ). Moreover, the presence of intact dietary proteins after weaning is important for the generation of regulatory T cells in the small intestine ( 8 ) and for the full development of immune activities during adulthood such as a protective response to infection ( 9 ), induction of nasal ( 10 ) and oral tolerance as well as allergic reactions ( 11 ). Thus, the role of intact dietary proteins in the maturation of immunological activity at the early stages of life is clear.…”
Section: Introductionmentioning
confidence: 99%
“…We observed that the impaired Th1 polarization in C57BL/6 Aa-fed mice is related to an immature state of antigen-presenting cells (APCs) in Aa-fed mice rather than an intrinsic defect in T cells. (Amaral et al, 2010). Phenotypical and functional analysis of APCs from Aa-fed mice revealed deficiencies in levels of costimulatory molecules (CD40 and CD80) as well as a poor ability to stimulate Th1 responses in vitro .…”
Section: Food Proteins In the Maturation Of Immune Systemmentioning
confidence: 99%
“…Se a dieta que recebem é artificial e sem macromoléculas (antigenfree), esses defeitos se tornam mais severos, e os animais não chegam sequer a desenvolver linfonodos (Haury et al, 1997). Na UFMG, Menezes, Faria e colaboradores mostraram que animais criados em gaiolas comuns, abertas, expostos aos micróbios do ambiente, mas que recebem uma dieta sem proteínas, balanceada com aminoácidos, desenvolvem defeitos imunológicos similares a animais "isentos de germes" (Menezes et al, 2006;Amaral et al, 2010).…”
Section: O Microbioma E a Dietaunclassified